2017
DOI: 10.1007/s11748-017-0870-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass for pediatric cardiac surgery

Abstract: The management of cardiopulmonary bypass for pediatric cardiac surgery is more challenging than that in adults due to the smaller size, immaturity, and complexity of the anatomy in children. Despite major improvements in cardiopulmonary bypass, there remain many subjects of debate. This review article discusses the physiology of cardiopulmonary bypass for pediatric and congenital heart surgery, including topics related to hemodilution, hypothermia, acid-base strategies, inflammatory response, and myocardial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
1
23
0
7
Order By: Relevance
“…Many intraoperative factors have been implicated in the development of AKI [2,17,18,20]. These factors include use of CPB, length of CPB, blood transfusions, and intraoperative hypotension.…”
Section: Intraoperativementioning
confidence: 99%
See 1 more Smart Citation
“…Many intraoperative factors have been implicated in the development of AKI [2,17,18,20]. These factors include use of CPB, length of CPB, blood transfusions, and intraoperative hypotension.…”
Section: Intraoperativementioning
confidence: 99%
“…These factors include use of CPB, length of CPB, blood transfusions, and intraoperative hypotension. Although CPB provides for continued perfusion of body organs during heart surgery, CPB use poses an inherent risk for remote organ damage including kidney damage [19,20].…”
Section: Intraoperativementioning
confidence: 99%
“…However, hypothermia can also cause challenges in this population including negatively affecting cellular membrane stability and ATP production and utilization and increasing coagulopathy (96). Hypothermia can also interfere with oxygen and glucose uptake in the brain, as well as distort the pH of blood (97,98). As such, the ideal temperature for congenital cardiac surgery is controversial and dependent upon the surgeon and the surgical procedure being performed (96).…”
Section: Temperature Managementmentioning
confidence: 99%
“…Immature myocytes provide a different challenge than mature myocytes to achieve maximum protection. Immature myocardial tissue is more resistant to ischemia, but more susceptible to myocardial edema associated with frequent cardioplegia administration (98). An international survey performed in 2011 revealed that del Nido cardioplegia was the most commonly used solution in North America with 32% of centers using it (100).…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…As modern medical technology develops, the number of patients undergoing cardiac surgery under cardiopulmonary bypass (CPB) has increased (1). CPB enables cardiovascular surgery to be safer and more practical, but complications from surgery can lead to a systemic inflammatory response (2).…”
Section: Introductionmentioning
confidence: 99%